The Effect of Livin' by Mandiri Application Service Quality on Customer Satisfaction: Study on PT Bank Mandiri (Persero) Tbk. Solo - Damayanti, Rosita Mei; Diah Pramesti; Moch Faizhal Dzaky (AKUMULASI: Indonesian Journal of Applied Accounting and Finance, 2023)
This research tries to understand the relationship between service quality and customer satisfaction on the Livin’ by Mandiri, a mobile-banking application of Bank Mandiri. The respondents are customers of the Bank Mandiri Solo UNS Branch office. The number of respondents is 100. The data were collected by questionnaire and test using SPSS 23. The result of this study shows that service quality factors such as tangibles, reliable, assurance, and empathy positively affect customer satisfaction. When the Livin’ by Mandiri application improves in terms of the tangibility, reliability, assurance, and empathy, customer satisfaction will increase. The variable of responsiveness has no significant effect on customer satisfaction. The subject of this research is an application that cannot literally become responsive to serve customers. This research result may be important as the policy implication for Bank Mandiri to make the customers able to use the application optimally.